플랫폼 자사우대(Self-preferencing) 규제이론의 한계와 실무상 쟁점 - 장품; Poom Jang (경쟁법연구, 2024)
최근 전 세계 경쟁당국이 문제 삼고 있는 온라인플랫폼의 자사우대(self-preferencing)는 온라인플랫폼 사업자가 자사 제품이나 서비스를 경쟁사보다 우대하는 행위를 의미하며, 시장지배력 남용의 주요 유형으로 논의된다. EU 구글쇼핑 사건, 아마존 사건, 네이버쇼핑 사건, 카카오모빌리티 사건 등 국내외 주요 사건을 통해서 규제 당국이 자사우대행위에 대해 접근하는 방식을 살펴볼 수 있다. 자사우대를 규제하는 근거로는 시장지배력 전이 우려, 플랫폼 중립성, 필수설비 이론 등이 제시되는데, 모두 이론상 적지 않은 한계가 있어 보인다. 실무적으로도 지배력 전이(leverage) 자체가 갖는 경쟁제한의 우려가 과다하게 평가될 수 있다는 점, 자사의 상품과 서비스를, 타사의 상품과 서비스보다 더 선호하고 우대하는 것은, 통상의 경제활동에서 ‘경쟁의 의도’로 인식되는 게 자연스럽다는 점, 자사 상품과 서비스가 우대가 되었는지, 우대가 되었다면 어느 정도 되었는지, 우대의 의도가 인정되는지, 우대의 기준이 무엇인지에 대해 합의된 기준을 특정하기 어렵다는 점 등이 존재한다. 최근 문제 된 온라인플랫폼의 자사우대 규제 사건들을 보면, 행위주체가 대형 온라인플랫폼 사업자라는 사실 외에 ‘자사우대 행위’를 차별적으로 취급하여 규제 대상으로 특정할 이론적, 법리적 근거가 불명확하며, 원칙적으로, 그리고 보편적으로 허용되는 영업활동이 ‘온라인플랫폼’ 영역에서 발생했다는 이유로 규제대상으로 포섭된다면, 이는 수범자의 예측가능성 침해와 영업활동 위축이라는 부작용으로 이어질 우려가 있다는 점을 고려하여 실무적인 보완이 필요할 것이다. Self-preferencing by online platforms, which refers to the practice of online platform operators favoring their own products or services over those of competitors, has recently become an issue for competition authorities around the world and is discussed as a major type of abuse of dominance. Major domestic and international cases, such as the EU Google Shopping case, Amazon case, Naver Shopping case, and KakaoMobility case, illustrate how regulators approach self-preferential behavior. The rationales for regulating self-favoritism include concerns about market power transfer, platform neutrality, and essential facilities theory, all of which have significant limitations in theory. In practice, the anti-competitive effects of leverage itself may be overestimated, and preferring and favoring one’s own goods and services over those of others is often recognized as a “competitive intent” in normal economic activity, That it is difficult to specify agreed-upon criteria for determining whether a company’s goods and services have been preferred, and if so, to what extent, whether the intent to prefer is recognized, and what the criteria for preferential treatment are, and that the abstractness and unclearness of remedial measures may inevitably lead to a reduction in performance competition. Based on the recent cases of self-favoritism regulation of online platforms, it is unclear whether there is a rational basis for treating ‘self-preferencing’ differently and targeting it for regulation, other than the fact that the actor is a large online platform operator. If business activities that are in principle and universally permissible are subject to regulation because they occur on an ‘online platform’, it is likely to lead to a loss of predictability and a chilling effect on business activities.